Penanggulangan Tindak Pidana Penyalahgunaan Dana Zakat Dalam Hukum Positif Di Indonesia - Rohman, Fadlur; Fitroh, Khoirul; Hermawan, Aries (Journal of Islamic Economics, Banking, and Social Finance, 2025)
This study examines the handling of criminal acts related to the misuse of zakat funds under Indonesian positive law, focusing on government-established zakat management institutions. It employs a normative research methodology using statute, case, and comparative approaches. The first finding reveals that cases of zakat fund misuse are addressed using Article 2(1) in conjunction with Article 3 of the Anti-Corruption Law. A key factor in applying these provisions is that the perpetrator's actions result in financial losses to the state. Another influencing factor is the approach taken by the Public Prosecutor (JPU) in framing the indictment, which primarily relies on the Anti-Corruption Law without referencing provisions in other relevant legislation, such as the Zakat Management Law. This is evident in the primary and subsidiary indictments, where the focus remains on anti-corruption provisions. The second finding highlights that, based on the systematic lex specialis principle, Articles 37 and 40 of the Zakat Management Law are more specific in addressing material, formal, and subject (adresat) aspects of the crime. Consequently, under the principle of systematic specificity, these provisions are more appropriate to apply in cases of zakat fund misuse than the general provisions of the Anti-Corruption Law. Therefore, the study concludes that the legal application by the Panel of Judges in such cases is flawed if it prioritizes the Anti-Corruption Law over the Zakat Management Law. In cases involving criminal acts in zakat management, the Zakat Management Law should serve as the primary legal framework.